Examining differences in menstrual and intimate care product use by race/ethnicity and education among menstruating individuals - Zota, Ami R.; Franklin, Elissia T.; Weaver, Emily B.; Shamasunder, Bhavna; Williams, Astrid; Siegel, Eva L.; Dodson, Robin E. (Frontiers in Reproductive Health, 2023)
Introduction United States consumers spend over two billion dollars a year on intimate care products. These products, along with scented menstrual products, are marketed for odor control, perceived “freshness,” and vaginal/vulvar cleanliness. However, these scent-altering products may increase exposure to carcinogenic and endocrine-disrupting chemicals. Prior research has not adequately characterized demographic differences in product use. The objective of our study is to examine racial/ethnic and educational differences in menstrual and intimate care product use among people who menstruate. Methods We pooled data from two US-based cross sectional studies to examine demographic characteristics and product use in 661 participants aged 18–54 years. Participants reported use of scented and unscented menstrual products (tampons, sanitary pads, and menstrual cups) and intimate care products (vaginal douches, sprays, wipes, and powders). We examined differences by race/ethnicity and education using log-binomial regression and latent class analysis (LCA), which can identify groups based on product use patterns. Results Our sample was 33.4% Black, 30.9% Latina, 18.2% White, and 16.2% another identity. Approximately half the population had a bachelor's degree or more; 1.4% identified as transgender and 1.8% as non-binary. In adjusted models, scent-altering products (i.e., scented menstrual and intimate care products) were more likely to be used by those with less formal education (p < 0.05). Unscented menstrual products were more likely to be used by those with more formal education. Compared to Black participants, White participants were more likely to use unscented tampons and menstrual cups and less likely to use douches and wipes (p < 0.05). Using LCA we identified two groups: one more likely to use scent-altering products, and a second more likely to use unscented menstrual products. Less education and older age, but not race/ethnicity, was significantly associated with membership in the group more likely to use scent-altering products. While sex/gender composition did not statistically vary across groups, all non-binary participants fell in the unscented menstrual product group. Discussion Lower educational attainment was consistently associated with greater use of scent-altering menstrual and intimate care products. Future research should examine associations between body odor stigma, product use, and health risks at intersections of race, class, and gender.